Value engineering study on drainage design in slope - Ting, Jude Mui Heng (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study evaluate the value of horizontal drain in slope using value engineering process. The main focus in this study is to achieve the high value of horizontal drain in slope. The usage of horizontal drain is one of the methods that used to lower the high ground water table and hence stabilize the slope. Several elements in the slope is evaluate and the horizontal drain in the slope is studied on its value. The value of the installation of horizontal drain are investigates through sets of different types of pipes. Others components in slope such as degree of slope, drainage filter and vegetations are studied as well. The combination of different components in the slope is analyzed. Total proposed of 48 alternative design using different combination are studied with their value. From the evaluations obtained from the research, it can be concluded that the pipe that being used in the initial design which is 75mm "Class D" UPVC can be replaced by HDPE Grade PN 10 which will increase the value as much as 13.42%. However, the recommendation is given to the combination of the alternative design which give the increase value as much as 15.77 % by replacement of slope degree from 25o to 35o and 75mm "Class D" UPVC to HDPE Grade PN 10. This study also found that with the increase of slope from 25o to 35o will cost 35.32 %more on vegetation which will only increase the value by 1.85%.